CRISPR/Cas12a Powered DNA Framework‐Supported Electrochemical Biosensing Platform for Ultrasensitive Nucleic Acid Analysis. Issue 12 (10th October 2021) - Su, Jing; Ke, Yuqing; Maboyi, Nokuzola; Zhi, Xiao; Yan, Sijia; Li, Fuwu; Zhao, Bo; Jia, Xiaolong; Song, Shiping; Ding, Xianting
Abstract: Nucleic acid analysis using ultrasensitive and simple methods is critically important for the early‐stage diagnosis and treatment of diseases. The CRISPR/Cas proteins, guided by a single‐stranded RNA have shown incredible capability for sequence‐specific targeting and detection. Herein, in order to improve and expand the application of CRISPR/Cas technology to the electrochemical interface‐based nucleic acids analysis, the authors develop a CRISPR/Cas12a powered DNA framework‐supported electrochemical biosensing platform via the cis and trans cleavage of Cas12a on the heterogeneous carbon interface (the existing publications which commonly adopted trans‐cleavage). Their solid‐liquid interface is first immobilized by 3D tetrahedral framework nucleic acids (FNAs) with specific DNA recognition probe. Based on the recognition of the complementary target through protospacer adjacent motif (PAM) confirmation and CRISPR‐derived RNA (crRNA) matching, the easily formed Cas12a/crRNA duplex can get access to the interface, and the cis and trans cleavage of Cas12a can be easily activated. In combination with the enzyme catalyzed reaction, they achieved an ultralow limit of detection (LOD) of 100 fm in HPV‐16 detection without pre‐amplification. Furthermore, the platform is compatible with a spike‐in human serum sample and has superior stability. Thus, their reported platform offers a practical, versatile, and amplification‐free toolbox for ultrasensitive nucleic acid analysis. Abstract : CRISPR/Cas12a powered DNA framework supported electrochemical biosensing platform via the cis and trans cleavage of Cas12a provide high accessibility of the Cas12a/crRNA and target to the report probe on the heterogeneous interface, meanwhile repelling adsorption of non‐specific report DNA, thus leading to an ultrahigh sensitivity without further signal amplification.